2008
DOI: 10.1063/1.3020692
|View full text |Cite
|
Sign up to set email alerts
|

Microwave attenuation of hydrogen plasma in carbon nanotubes

Abstract: Nitrogen and hydrogen plasma treatments of multiwalled carbon nanotubes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
(28 reference statements)
0
6
1
Order By: Relevance
“…It is clear that the microwave absorption coefficient of the magnetized hydrogen plasma moves from low to high frequencies when the magnetic field strength increases, which is completely different from the results obtained in Ref. 9. However, for = 90°the absorption peak decreases with increasing cyclotron frequency and moves from low to high frequencies, as shown in Fig.…”
Section: -3contrasting
confidence: 67%
See 1 more Smart Citation
“…It is clear that the microwave absorption coefficient of the magnetized hydrogen plasma moves from low to high frequencies when the magnetic field strength increases, which is completely different from the results obtained in Ref. 9. However, for = 90°the absorption peak decreases with increasing cyclotron frequency and moves from low to high frequencies, as shown in Fig.…”
Section: -3contrasting
confidence: 67%
“…5 On the other hand, CNTs produced via HiPco process have been extensively explored for potential applications in electromagnetic shielding or absorbing materials ͑around 2.45 GHz͒. [8][9][10][11][12][13][14][15] The HiPco process is a technique for catalytic production of CNTs in a continuous-flow gas phase using CO as the carbon feedstock and Fe͑CO͒ as the ironcontaining catalyst precursor. Imholt et al 11 and Wadhawan et al 12 reported that CNTs under vacuum ͑less than 10 −5 Torr͒ irradiated with a microwave field of 300 W produced a visibly bright plasma accompanied by rapid degassing of the CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, finding an alternative way to fast-anneal VACNTs has become significant. Recently, CNTs have been found to display strong microwave absorption accompanied by a rapid temperature increase to above 1550 °C. The strong microwave absorption by CNTs has recently attracted considerable interest for both theoretical research and potential applications, especially for CNT functionalizations, the mechanism being still open to question though. In the present study, we report the application of microwave radiation for VACNT fast annealing; the annealed CNTs show great improvements in mechanical and electrical properties.…”
mentioning
confidence: 99%
“…For different external magnetic field intensities, the microwave absorption coefficients of the hydrogen plasma embedded inside HiPco CNTs have been calculated based on Eqs. ( 8), ( 9), ( 14), ( 15), ( 18), (21), and (22) in the frequency range from 0.3 GHz to 30.0 GHz.…”
Section: Resultsmentioning
confidence: 99%